The importance sports activities have over the quality of life in the adult population (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
The quality of life is a wide spread concept which essentially handles the overall prosperity within society, the importance of it increasing starting with the 1970s, together with the social studies research. An European poll concerning the quality of life in Europe (2003-2007), performed by the European Life and Work Condition Improvement Foundation, noted the existence of some major differences between countries and social groups, as far as numerous aspects of quality of life are concerned. Thus, we can see that social groups with a below average quality of life must progress in a faster pace than the leader groups. In Romania, based on a general evaluation, we can state that the quality of life level is a modest one, this statement being the more valid as we take into consideration the economic standard - from macro-economic indicators of living standards (GDP/capita, Finances available to the population) and average income/household to life expectancy at birth indexes (MÄƒrginean, I., 2010, pp. 231-237). The main component of the quality of life, health, can be maintained and improved by performing sports activities, where the main element is performing workouts, which, applied on a long term, improves the physical and mental health, having a positive contribution on the learning and personal development processes and to reducing the risk of physical and psychological conditions associated with the modern lifestyle.